Management of Fan Engagement in Motor Sports: A Case Study of Fan Engagement and Legitimacy of Players in The Bahrain Grand Prix - Soleman Mozammel; Israa Salah Abdulla (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The objective of this research inquiry is to analyse the intricacies involved in the administration of fan engagement within the realm of motor sports, specifically focusing on the Bahrain Grand Prix. The study examines the independent variables of entertainment, integration, and social interaction, while the dependent variable focuses on the perception of legitimacy among players. This study additionally examines the mediating influence of fan engagement and the moderating effect of sports motivation. The chosen research methodology is quantitative in nature, and the survey strategy has been employed as the means of gathering data. The data was subjected to analysis using Smart-PLS and SPSS software. The findings of the study have demonstrated a noteworthy influence of entertainment on the level of fan engagement and the perception of legitimacy regarding sports players. The perception of sports players' legitimacy is significantly influenced by the level of fan engagement. Furthermore, the integration of various elements and the interaction between sports and fans have a substantial influence on the level of engagement exhibited by fans, as well as the perception of legitimacy surrounding sports players. Nevertheless, the moderation of sports motivation holds little significance, whereas the mediation of fan engagement carries substantial importance.